Saccharomyces cerevisiae U1 small nuclear RNA secondary structure contains both universal and yeast-specific domains. - Kretzner, L (1990)
The five small nuclear RNAs (snRNAs) involved in mammalian pre-mRNA splicing (U1, U2, U4, U5, and U6) are well conserved in length, sequence, and especially secondary structure. These five snRNAs from Saccharomyces cerevisiae show notable size and sequence differences from their metazoan counterparts. This is most striking for the large S. cerevisiae U1 and U2 snRNAs, for which no secondary structure models currently exist. Because of the importance of U1 snRNA in the early steps of "spliceosome" assembly, we wanted to compare the highly conserved secondary structure of metazoan U1 snRNA (approximately 165 nucleotides) with that of S. cerevisiae U1 snRNA (568 nucleotides). To this end, we have cloned and sequenced the U1 gene from two other yeast species possessing large U1 RNAs. Using computer-derived structure predictions, phylogenetic comparisons, and structure probing, we have arrived at a secondary structure model for S. cerevisiae U1 snRNA. The results show that most elements of higher eukaryotic U1 snRNA secondary structure are conserved in S. cerevisiae. The hundreds of "extra" nucleotides of yeast U1 RNA, also highly structured, suggest that large insertions and/or deletions have occurred during the evolution of the U1 gene.